A proteção à parentalidade no direito previdenciário contemporâneo brasileiro - Ribeiro, Juliana de Oliveira Xavier (2024)
With the global risk society, by Ulrich Beck, and a third way policy, by Anthony Giddens, the development of this study has become even more important, whose main purpose is to demonstrate the possibility of selective parental leave as a new benefit to the Brazilian family, both for parents to take care of their children and adolescents, and for children to take care of their elderly and incompetent parents. In the field of social security funding, there is a great uproar and discussion regarding the sustainability of the social security system in the face of the creation of a new social security provision. In this question, the question is whether Taxation 4.0, through the taxation of robots, and the Green Tax would fit into the diversity of the financing base of the Social Security System, to meet the counterpart requirement, described in article 195, § 5º, of the Federal Constitution of 1988. This research uses the qualitative method, based on national and international doctrines and the purposes of elucidating the issues of postmodernity in the risk society and its impacts on the Brazilian family, especially parenting, as well as a way of demonstrating that, in fact, the family, as the essential basis of society, is in need of state protection, even in the face of the current Social Security crisis